Chorion Alterations in Eyed-Stage Salmonid Eggs Farmed in La Araucanía, Chile: A Retrospective Study - Iván Valdebenito; Elías Figueroa; Matías Valdebenito; Luis Paiva (Animals, 2021)
The chorion is the primary envelop that protects the fish embryo against mechanical actions, pathogens, and abrupt changes in physical and chemicals conditions of the incubation medium. During embryo development, chorion alterations are not rare, but the occurrence of these is scarcely reported. Increased frequency of chorion alterations can result in increased embryo mortality and thus decreased reproductive performance and losses for fish farms. In this study, we characterize different chorion alterations observed in samples collected over 14 years from 12 salmon and trout farms located in the region of La Araucanía in southern Chile, which sent live eyed-stage embryos (‘eyed-eggs’) for quality analysis to our laboratory. We found soft chorion as the most common alteration observed, being present in the whole 14-year series analyzed in Atlantic Salmon (Salmo salar) and affecting up to 35.0% of the samples examined in a year. This alteration also affected up to 20.0 and 5.7% of Coho Salmon (Oncorhynchus kisutch) and Rainbow Trout (Oncorhynchus mykiss) samples analyzed in a year, respectively. We also found an increase of other chorion alterations, including perforated and white-spotted chorion in Atlantic and Coho Salmon, in the last 8 years. Among the three species, Rainbow Trout exhibited fewer chorion alterations. As the embryonated eggs analyzed here were obtained from broodstocks maintained under standard industrial conditions, these alterations might be linked to changes in environmental conditions affecting the incubation water that need to be further investigated.